The influence of the school principal's transformational leadership style and work environment on the job satisfaction of state junior high school teachers in Cipayung district - Indah Nurul Izzati; Muhammad Taufiq Amir (Sean Institute, 2024)
Education has a crucial role in developing individual potential and the progress of a nation. Teachers as the main agents in the educational process play an important role in achieving educational goals. In optimising teacher functions, the principal’s leadership and the work environment in the school are critical factors that influence teachers’ performance and job satisfaction. Therefore, it is necessary to carry out in-depth research to identify the influence of the principal’s transformational leadership style and work environment on teacher job satisfaction in State Junior High Schools in Cipayung District. The research design used in this research is quantitative. The sample used was 130 respondents. Multiple regression analysis was used to test the hypotheses in this research. From the research results, it can be concluded that the principal’s transformational leadership style has a positive and significant influence on the job satisfaction of State Junior High School teachers in Cipayung District, the work environment has a positive and significant influence on the job satisfaction of State Junior High School teachers in Cipayung District, as well as the principal’s transformational leadership style and the work environment have a positive and significant effect together (simultaneously) on the job satisfaction of State Junior High School teachers in Cipayung District.